Future expectations of venezuelan migrants stranded in colombia during the pandemic - Aliaga Sáez, Felipe; Díaz Medina, Franklin (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article analyzes the future expectations of Venezuelan migrants who are confined during the pandemic. The field work is carried out in the year 2020 through interviews in the shelter of the Scalabrinian Mission in Cúcuta, Colombia. We address the idea of illusion and dissimulation by A. Sayad, future expectations from F. Aliaga, and the concept of risk with U. Beck. It is concluded that people, despite the difficulties, maintain the hope of reaching a destination in which to improve their quality of life and be able to get ahead.